Evaluation of antiulcerogenic activity of combination of Aloe vera and Aegle marmelos in indomethacin induced gastric ulcers - Hugar, Leela; H., Ramesh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Most important adverse effect of NSAID is peptic ulceration. Even though H2 blockers and proton pump inhibitors are effective in preventing NSAID associated peptic ulceration, they are not without side effects. Hence there is a need for drugs which are effective in preventing NSAID induced peptic ulcer without producing side effects. Two plant products Aloe vera leaf extract and Aegle marmalos leaves are commonly used in Indian traditional medicine for treatment of peptic ulcers. Hence this study is undertaken to assess the antiulcerogenic potential of combination of these two drugs in comparison with ranitidine in preventing NSAID induced peptic ulcers. Methods: 18 albino rats were divided into 3 groups of 6 rats each. Group A: received ulcerogen only. Group B: pretreated with ranitidine before exposing to ulcerogen. Group C: pretreated with combination of Aloe vera and Aegle marmelos before exposing to ulcerogen. Two doses of indomethacin were administered at an interval of 15 hrs. Animals were sacrificed 6 hrs after the second dose of Indomethacin. Number of ulcers was noted, and ulcer index was calculated. Results: There was significant reduction in total score, mean score and ulcer index in ranitidine pretreated group and test compound group as compared to control group. Even though the total score and ulcer index in test group were lesser as compared to standard control group, it was not statistically significant. Conclusions: Combination of Aloe vera leaf extract and Aegle marmelos leaf extract produced very significant protection against indomethacin induced gastric ulcer.